Xanthophylls, Phytosterols and Pre‐β1‐HDL are Differentially Affected by Fenofibrate and Niacin HDL‐Raising in a Cross‐Over Study. Issue 12 (26th September 2013) - Niesor, Eric J.; Gauthamadasa, Kekulawalage; Silva, R. A. Gangani D.; Suchankova, Gabriela; Kallend, David; Gylling, Helena; Asztalos, Bela; Damonte, Elisabetta; Rossomanno, Simona; Abt, Markus; Davidson, W. Sean; Benghozi, Renee
Abstract: Fenofibrate and extended‐release (ER) niacin similarly raise high‐density lipoprotein cholesterol (HDL‐C) concentration but their effects on levels of potent plasma antioxidant xanthophylls (lutein and zeaxanthin) and phytosterols obtained from dietary sources, and any relationship with plasma lipoproteins and pre‐β1‐HDL levels, have not been investigated. We studied these parameters in 66 dyslipidemic patients treated for 6 week with fenofibrate (160 mg/day) or ER‐niacin (0.5 g/day for 3 week, then 1 g/day) in a cross‐over study. Both treatments increased HDL‐C (16 %) and apolipoprotein (apo) A‐I (7 %) but only fenofibrate increased apoA‐II (28 %). Lutein and zeaxanthin levels were unaffected by fenofibrate but inversely correlated with percentage change in apoB and low‐density lipoprotein cholesterol and positively correlated with end of treatment apoA‐II. ApoA‐II in isolated HDL in vitro bound more lutein than apoA‐I. Xanthophylls were increased by ER‐niacin (each ~30 %) without any correlation to lipoprotein or apo levels. Only fenofibrate markedly decreased plasma markers of cholesterol absorption; pre‐β1‐HDL was significantly decreased by fenofibrate (−19 %, p < 0.0001), with little change (3.4 %) for ER‐niacin. Although fenofibrate and ER‐niacin similarly increased plasma HDL‐C and apoA‐I, effects on plasma xanthophylls, phytosterols and pre‐β1‐HDL differed markedly, suggesting differences in intestinal lipidation of HDL. In addition, the in vitro investigations suggest an important role of plasma apoA‐II in xanthophyll metabolism.